DETERMINATION OF OCCLUSAL VERTICAL DIMENSION IN A SECTION OF PAKISTANI POPULATION USING CRANIOFACIAL MEASUREMENTS - Muhammad Irfan Majeed; Muhammad Afzal; Muhammad Kashif (Journal of University Medical & Dental College, 2015)
ABSTRACT: The accurate reproducible maxillo-mandibular relation of edentulous patient can be successfully determined by measuring various craniofacial landmarks. OBJECTIVE: The objective of this study was to check the authenticity of various facial measurement theories for the determination of occlusal vertical dimension (OVD) and their implementation among Pakistani population. MEASUREMENTS: Measurements were taken on 300 fully dentate patients with their teeth in centric occlusion. RESULTS: Results were statistically analyzed by using SPSS version 20. There were three measurements, right corner of the lips to left corner of the lips along the curvature, outer canthus of the right eye to the inner canthus of the left eye and inner canthus of the right eye to inner canthus of the left eye multiply by two, which had close approximation to original occlusal vertical dimension among Pakistani population as compared to other measurements and it also confirms the racial difference in the various parts of the world.